Contribution of accounting to services outsourcing management in hospitals - Beuren, Ilse Maria; Manfroi, Leossania; Dagostini, Luciane (Revista de Administração da UFSM, 2016)
The study aims to determine the contribution of accounting to the management of services outsourcing in hospitals in Santa Catarina. Was performed descriptive research through a survey with the managers of the hospitals affiliated with Federação dos Hospitais de Santa Catarina (FEHOESC), having as the sample 24 responding hospitals. For the survey was used the questionnaire developed by Lamminmaki (2008), composed of four factors that may influence the participation of accounting and the sophistication of accounting systems in the management of services outsourcing. The results indicate that the factors analyzed (existence of internal accounting, existence of controllership department, size of the hospitals and managers training) contribute in a weak way to the accounting participation and to the sophistication of accounting systems to the management of services outsourcing. It is concluded that the contribution of accounting to services outsourcing management is weak in the hospitals surveyed. This result instigates investigate the reasons for the apathy found, since accounting should be an important source of information for the management of services outsourcing in hospitals.